Одговори незапада на руски рат у Украјини: Учење из Индонезије - Dharmaputra, Radityo (Journal of Regional Security, 2023)
The full-scale Russian invasion on February 24th has brought diverse responses in different parts of the world. While the so-called “Western” world responded with strong condemnation, sanctions, and military helps, the “non-Western” world responded more cautiously and hesitantly. Using Indonesia, the current chair of G20 and one of the leading voices in the developing countries, this study traces the diverse narratives of Indonesian political elites and public intellectuals on how to interpret the war in Ukraine, the relationship between Russia and the “non-Western” world, and the NATO factors. Specifically, this contribution looks at how the lack of knowledge about Russia and Ukraine (and Eastern Europe in general), coupled with the strong anti-Western sentiment, has created a more pro-Russian sentiment in the Indonesian narratives about the war.